QRcode Verifikasi Sertifikat Sebagai Bukti Keabsahan Dokumen dalam Bidang Pendidikan - Febriyanto, Erick; Triyono, Triyono; Rahayu, Nina; Nurbaiti, Resti (Technomedia Journal, 2020)
The falsification of certificates or documents is running rampant in Indonesia, especially in urban areas. The lack of public knowledge about the authenticity of a document and the difficulty of verifying documents are the main factors in the fraud of this document forgery. The purpose of this document verification system research is to facilitate the public in verifying documents and minimizing the falsification of duplicate or modification documents, and reducing the number of certificate and document fraud. The application is designed based on web and mobile apps (Android & IOS), making it easier to use and develop. This research uses data collection research methods which include observation, interviews, and literature study. Interviews were carried out in a socialization manner to the public so that they could find out to what extent their knowledge of cases of forgery of this document, while to analyze the system using the SWOT analysis method and blackbox testing. This verification system is really needed by the community and government, so that in the creation of web applications and mobile apps it is designed in such a way that it can produce applications that are user friendly, innovative, creative, and informative. The research results are also directed to obtain the protection of Intellectual Property Rights (IPR), both in the form of Copyright and Industrial Property Rights. Key Words : Certificate, QR Code, Verification, SWOT, Blackbox Testing